2022
DOI: 10.1371/journal.pgph.0000180
|View full text |Cite
|
Sign up to set email alerts
|

Integrating services for HIV and multidrug-resistant tuberculosis: A global cross-sectional survey among ART clinics in low- and middle-income countries

Abstract: Tuberculosis (TB) is the leading cause of death among PLHIV and multidrug-resistant-TB (MDR-TB) is associated with high mortality. We examined the management for adult PLHIV coinfected with MDR-TB at ART clinics in lower income countries. Between 2019 and 2020, we conducted a cross-sectional survey at 29 ART clinics in high TB burden countries within the global IeDEA network. We used structured questionnaires to collect clinic-level data on the TB and HIV services and the availability of diagnostic tools and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…With work in progress for 11 papers addressing gaps in the literature, IeDEA's 2020 site assessment survey promises to generate more scientific productivity than IeDEA's prior consortium-wide general site assessment surveys [2][3][4] and specialized surveys focused on specific patient populations (e.g., pediatrics, pregnant and postpartum women) [8] and areas of service delivery (e.g., tuberculosis, cancer, mental health disorders, etc.) [9][10][11][12][13][14][15]. Data collected through IeDEA's 2020 site assessment survey are being used in studies addressing the following aims: 1.…”
Section: Discussionmentioning
confidence: 99%
“…With work in progress for 11 papers addressing gaps in the literature, IeDEA's 2020 site assessment survey promises to generate more scientific productivity than IeDEA's prior consortium-wide general site assessment surveys [2][3][4] and specialized surveys focused on specific patient populations (e.g., pediatrics, pregnant and postpartum women) [8] and areas of service delivery (e.g., tuberculosis, cancer, mental health disorders, etc.) [9][10][11][12][13][14][15]. Data collected through IeDEA's 2020 site assessment survey are being used in studies addressing the following aims: 1.…”
Section: Discussionmentioning
confidence: 99%
“…With work in progress for 11 papers addressing gaps in the literature, IeDEA's 2020 site assessment survey promises to generate more scientific productivity than IeDEA's prior consortium-wide general site assessment surveys [2][3][4] and specialized surveys focused on specific patient populations (e.g., pediatrics, pregnant and postpartum women) [10] and areas of service delivery (e.g., tuberculosis, cancer, mental health disorders, etc.) [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…For the inclusion criteria, it may be possible that a tuberculosis diagnosis was incorrectly documented. It may also be possible that some patients had drug resistant tuberculosis and were not receiving rifampicin; however, such treatment is often provided off‐site in our setting [ 31 ]. To examine these potential sources of bias, we conducted subgroup analyses limited to those with documentation of HRZE and found that results were consistent with the main analysis.…”
Section: Discussionmentioning
confidence: 99%